Controle da mancha angular do feijoeiro com uso de fungicidas e seu efeito na produção das plantas - Deman, Luis Alfredo Raue; Maringoni, Antonio Carlos [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2012)
The angular leaf spot of dry bean caused by the fungus Phaeoisairopsis griseola is a very important disease on dry bean crops in Brazil. In propitious weather conditions, susceptible cultivars have significant losses due to this disease. In these conditions, fungicide usage is an important step for angular leaf spot management. Since the effects of this method of control on plant physiology are not known, this study had the following objectives: a) Verify the action of fungicide in physiological changes in dry beans (photosynthesis rate and stomatal conductivity); b) evaluate the efficacy of some fungicides for the control of angular leaf spot; and c) examine the effects of these fungicides on other agronomic parameters; weight of 100 grains, number of grains per pod and number of pods per plant. The dry bean cultivar used in this study was Perola. Four trials were conducted, two in a net greenhouse and two trials under field conditions. A spray of piraclostrobin, tebuconazol and tebuconazol+ trifloxistrobin increased photosynthesis rates, although stomatal conductivity was not changed. In addition, sprays of tebuconazol, piraclostrobin, metiram+piraclostrobin and azoxistrobin provided better levels of disease control and also higher weight of 100 grains, with the exception of azoxystrobin for this parameter.
Control of angular leaf spot on dry beans with fungicides and its effect on plant production
Keywords: Chemical control; Phaeoisairopsis griseola; Phaseolus vulgaris L.